2018
DOI: 10.1002/smll.201703822
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Zr‐MOF as Fluorescence Turn‐On Probe for Real‐Time Detecting H2S Gas and Fingerprint Identification

Abstract: The development of fluorescence turn-on probes for selectively sensing toxic gases and visualization identification of fingerprints is significantly important for society security and human health. Here, Zr is used as the metal center and 1,3,6,8-tetra (4-carboxylphenyl) pyrene (TBAPy) and tetrakis(4-carboxyphenyl)porphyrin (TCPP) as double linkers to synthesize a novel Zr(TBAPy) (TCPP) material. Results indicate that Zr(TBAPy) (TCPP) can be used as a fluorescence turn-on probe for highly selective and sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 50 publications
0
37
0
2
Order By: Relevance
“…From the observed results distinct ridge details and enhanced properties were compared with traditional FP powders. In the same year, the research conducted by Sébastien et al [60] and Guo et al [61] confirmed the futuristic enhancement materials of MOFs.…”
Section: Long Wave Uv Spectroscopymentioning
confidence: 83%
“…From the observed results distinct ridge details and enhanced properties were compared with traditional FP powders. In the same year, the research conducted by Sébastien et al [60] and Guo et al [61] confirmed the futuristic enhancement materials of MOFs.…”
Section: Long Wave Uv Spectroscopymentioning
confidence: 83%
“…Metal organic frameworks (MOFs) offer highly selective and sensitive detection of H 2 S because of possessing chemical stability, custom tuning of porosity and functionalities, and various pre- or post-synthetic modifications to the structural framework [ 173 ]. Guo et al [ 174 ] synthesized a MOF material named as Zr(TBAPy) 5 (TCPP) using a solvothermal method, where Zr is the metal center, and 1,3,6,8-tetra(4-carboxylphenyl) pyrene (TBAPy) and tetrakis(4-carboxyphenyl) porphyrin (TCPP) act as double linkers. The prepared Zr(TBAPy) 5 (TCPP) exhibited well-shaped shuttle structures with a particle size of about 100 nm as seen from the transmission electron microscope (TEM) image ( Figure 14 D).…”
Section: Recent Advances In H 2 S Gas Detectionmentioning
confidence: 99%
“…( F ) Fluorescent enhancement response of the fabricated sensor under increasing S 2− concentration. Figures adapted with permission from [ 174 ], Copyright 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.…”
Section: Figurementioning
confidence: 99%
“…MOFs also belong to another class of porous materials with uniform pore size are called molecular sieves (Caro, 2016; Liu et al, 2018). Furthermore, fluorescent MOFs (Allendorf, Bauer, Bhakta, & Houk, 2009) have shown potential applications in sensing of ions (Zhao, Yang, Liu, & Ma, 2016), gases (Guo, Wang, & Cao, 2018; Lin, Liu, Ye, Li, & Zhang, 2016), and vapors (Du et al, 2018; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%